Shared book reading as a context for language intervention for children with Down syndrome: a mini-review - Jeremic, Mirjana; Stojanovik, Vesna; Burgoyne, Kelly; Pagnamenta, Emma (Frontiers in Psychology, 2023)
Acquiring language and communication skills is one of the biggest challenges for children with Down syndrome (DS). However, few evidence-based interventions exist to enhance the development of language and communication in this population. Shared book reading (SBR) is well-established as an effective intervention for language and communication development of typically developing children, and evidence of the possible effectiveness of this approach for those at risk of language difficulties is emerging. This paper provides a mini-review of the existing evidence for SBR in relation to language and communication outcomes for young children with DS. A systematic literature search was conducted with the following inclusion criteria: children with Down syndrome aged 0-6;11 years, SBR, language or communication outcomes. The results show that interventions which incorporate SBR strategies are associated with improved language and communication outcomes for young children with DS, improved parental sensitivity, and continuing implementation of SBR strategies following intervention instruction. However, evidence is limited in scope, of low quality, including mostly single case studies, with only one study having a control group. We conclude that although SBR may hold promise as a possible intervention, further research is essential to establish what specific components of SBR intervention are most effective for young children with DS and what further adaptations are needed to accommodate the cognitive profile and variability within this population.